Shallow seismic damage and structural inheritance at the onset of faulting - G. Pozzi; A. Ceccato; K. Wemmer; M. Hueck; S. Aretusini; E. Spagnuolo; A. Zappone; M.A. Meier; M. Cocco (Earth and Planetary Science Letters, 2026)

Genomic characterization of two Xanthomonas phaseoli pv. phaseoli strains of Italian origin reveals novel TAL effectors and putative susceptibility gene targets - A. Gaiti; G. M. Balestra; N. S. Iacobellis; E. Avite; C. M. Pozzi; D. Bulgari; M. Saracchi; A. Kunova; P. Cortesi; M. Pasquali (Journal of Plant Pathology, 2026)

KPC-producing Klebsiella pneumoniae in Switzerland from 2024 to 2025: comparative genomics and cefiderocol resistance mechanisms analyses - Jacqueline Findlay; Patrice Nordmann; R Lienhard; L Vonallmen; C Schilt; A Scherler; K Lucke; M Jutzi; M Reichmuth; U Schibli; C Fricker; S Pranghofer; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Biomechanical Simulations Informed by Multimodal Measurements Link Symptoms to Glenohumeral Joint Forces Across Healthy and Pathological Rotator Cuffs - Sarah M. Barron; Joseph J. King; Federico Pozzi; Jennifer A. Nichols (Annals of Biomedical Engineering, 2026)

In vitro activity of β-lactamase inhibitors avibactam, relebactam and vaborbactam in combination with aztreonam against metallo-β-lactamase producing Escherichia coli clinical isolates - Clément Viguier; Samanta Freire; Maxime Bouvier; Christophe Le Terrier; Laurent Poirel; A. Westers; M. Imperiali; L. Pozzi; D. Balzari; G. Vaninetti; C. Cirillo; V. Gaia; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Tracking Aeromonas caviae and Pseudomonas aeruginosa in a mixed-use catchment with source attribution, health hazards, and microbial mixing assessments - Adrien C. M. Pozzi; Angélique Dominguez-Lage; Baptiste Luton; Laurence Marjolet; Delphine Mouniée; Emmanuelle Bergeron; Matthieu Masson; Cécile Miège; Marina Coquery; Pauline Dusseux; Nicolas Robinet; Véronica Rodriguez-Nava; et al. (Environmental Science and Pollution Research, 2025)

Climate change and plant genomic plasticity - Carlo M. Pozzi; Angelo Gaiti; Alberto Spada (Theoretical and Applied Genetics, 2025)
Key message Genome adaptation, driven by mutations, transposable elements, and structural variations, relies on plasticity and instability. This allows populations to evolve, enhance fitness, and adapt to challenges like climate change. Abstract Genomes adapt via mutations, transposable elements, DNA structural changes, and epigenetics. Genome plasticity enhances fitness by providing the genetic variation necessary for organisms to adapt their traits and survive, which is especially critical during rapid climate shifts. This plasticity often stems from genome instability, which facilitates significant genomic alterations like duplications or deletions. While potentially harmful initially, these changes increase genetic diversity, aiding adaptation. Major genome reorganizations arise from polyploidization and horizontal gene transfer, both linked to instability. Plasticity and restructuring can modify Quantitative Trait Loci (QTLs), contributing to adaptation. Tools like landscape genomics identify climate-selected regions, resurrection ecology reveals past adaptive responses, and pangenome analysis examines a species’ complete gene set. Signatures of past selection include reduced diversity and allele frequency shifts. Gene expression plasticity allows environmental adaptation without genetic change through mechanisms like alternative splicing, tailoring protein function. Co-opted transposable elements also generate genetic and regulatory diversity, contributing to genome evolution. This review consolidates these findings, repositioning genome instability not as a mere source of random error but as a fundamental evolutionary engine that provides the rapid adaptive potential required for plant survival in the face of accelerating climate change.

Four unusual mortality events of seabirds in the Patagonian Sea, 2000–2006: species affected and possible causes - Marcela M. Uhart; Ralph E. T. Vanstreels; Flavio Quintana; Belén Mattera; Nora Montoya; Leonardo Guzman; Hernan Pacheco Valles; Gemita Pizarro; Carolina A. Marull; Luciana Pozzi; Torsten Mörner; Pablo García-Borboroglu; et al. (Polar Biology, 2025)
The Patagonian Sea is a highly productive marine ecosystem and a hotspot for seabird diversity and density in the Southwest Atlantic Ocean. Reports of unusual mortality events are relatively scarce in this region, likely due to under detection and investigation. In this study, we report on four unusual mortality events affecting seabirds in the Patagonian Sea from 2000 to 2006. Events 1 and 2 occurred at Golfo Nuevo and Chubut coast, Argentina in September–December 2000, affecting at least 4550 seabirds, mainly Magellanic penguins ( Spheniscus magellanicus ). Event 3 occurred at the Falkland/Malvinas Islands during December 2002–January 2003, affecting at least 3500 seabirds, mainly gentoo penguins ( Pygoscelis papua ). Event 4 occurred at Punta Loma and Punta León, Argentina, in November 2006, affecting at least 57 seabirds, mainly kelp gulls ( Larus dominicanus ). The aetiology of Events 1 and 2 could not be determined, but malnutrition/starvation and paralytic shellfish poisoning, respectively, were identified as potential causes. Pathological findings and toxicological testing supported paralytic shellfish poisoning as the cause of Events 3 and 4. Our results illustrate how identifying the occurrence, cause and extent of unusual mortality events affecting seabirds can present significant challenges. Moreover, our investigations of the events display variations in timeliness and completeness, and our lack of certainty on aetiology reflects the shortcomings often faced in remote locations and low resource settings. Technological advances, such as smartphones, increased public awareness and connectivity, coupled with more and better equipped protected areas and diagnostic laboratories will likely aid in overcoming difficulties from past decades.

Combined resistance mechanisms leading to high-level of cefiderocol resistance among NDM-like producing E. coli ST167 clinical isolates - Mustafa Sadek; Juan Bosch Duran; Trinad Chakraborty; Laurent Poirel; R. Lienhard; L. Vonallmen; C. Schilt; A. Scherler; K. Lucke; M. Jutzi; M. Reichmuth; V. Slutter; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Summary Purpose A series of NDM-producing Escherichia coli ST167 clinical isolates exhibiting resistance to cefiderocol (FDC), with no previous exposure to this antibiotic, were analyzed in this study. Methods The antimicrobial susceptibility testing and phenotypic detection of resistance patterns (Rapid Cefiderocol NP test and MIC determination) were performed for all tested isolates. Their entire genomes were sequenced by using the Illumina MiSeq platform and high-quality reads were de-novo assembled using the CLC Genomic Workbench. Genome-sequence based characteristics were analyzed using bioinformatics tools. Results All NDM-producing E. coli ST167 isolates showed a high level of resistance to FDC (MICs being 64 or > 64 mg/L). The chromosomally located cirA gene, encoding a catecholate siderophore receptor in E. coli , was truncated in all FDC-resistant isolates due to a frameshift mutation (S90Y), leading to CirA-deficient isolates. A four amino acid insertion (YRIN) was also identified after residue 333 in the PBP3 protein sequence of all E. coli isolates. Among them, a single FDC-resistant NDM-5-producing E. coli isolate (1006) was additionally resistant to aztreonam/avibactam (AZA MIC of 8 mg/L). When analyzed against the genome of another FDC resistant NDM-5 producing E. coli ST167 containing a YRIN insertion in the PBP3, and exhibiting decreased susceptibility to AZA, the broad-spectrum ß-lactamase CMY-42 was identified. Conclusion We identified a variety of NDM-producing E. coli isolates exhibiting high level of resistance to FDC as a result of the combined effect of CirA deficiency, along with production of NDM-type enzymes. The spread of such resistance phenotype across Europe poses great concern on the clinical efficacy of this novel drug. Additionally, the identification of an FDC- and AZA-resistant NDM-5 producing E. coli isolate represents one of the ultimate evolutions with a possible step towards pan-resistance.

Near real-time soybean phenology detection using proximally sensed hyperspectral canopy reflectance and machine learning methods - Nicolás Rigalli; Enrique Montero Bulacio; Martín Romagnoli; Juan M. Enrico; Silvina Bacigaluppo; Ricardo Pozzi; Raquel L. Chan; María E. Otegui; Margarita Portapila (International Journal of Remote Sensing, 2025)

Exploring frictional properties of upper plate fault reactivation in subduction zones: The Atacama Fault System in northern Chile - Yerko González; Gabriel González; Elena Spagnuolo; Giacomo Pozzi; Erik Jensen; Stefano Aretusini; Anja M. Schleicher (Earth and Planetary Science Letters, 2024)

Plant developmental oddities - Carlo M. Pozzi; Vittoria F. Brambilla; Angelo Gaiti; Alberto Spada (Planta, 2024)
Main conclusion Plants lacking shoot apical meristem develop with unique body shapes, suggesting rewiring of developmental genes. This loss of the meristem is likely influenced by a combination of environmental factors and evolutionary pressures. Abstract This study explores the development of plant bodies in three families (Podostemaceae, Lemnaceae, and Gesneriaceae) where the shoot apical meristem (SAM), a key structure for growth, is absent or altered. The review highlights alternative developmental strategies these plants employ. Also, we considered alternative reproduction in those species, namely through structures like turions, fronds, or modified leaves, bypassing the need for a SAM. Further, we report on studies based on the expression patterns of genes known to be involved in SAM formation and function. Interestingly, these genes are still present but expressed in atypical locations, suggesting a rewiring of developmental networks. Our view on the current literature and knowledge indicates that the loss or reduction of the SAM is driven by a combination of environmental pressures and evolutionary constraints, leading to these unique morphologies. Further research, also building on Next-Generation Sequencing, will be instrumental to explore the genetic basis for these adaptations and how environmental factors influence them.

Intelligent Radiation: A review of Machine learning applications in nuclear and radiological sciences - Abbas J. Jinia; Shaun D. Clarke; Jean M. Moran; Sara A. Pozzi (Annals of Nuclear Energy, 2024)

Molecular analysis of metallo-beta-lactamase-producing Pseudomonas aeruginosa in Switzerland 2022–2023 - Jacqueline Findlay; Otavio Hallal Ferreira Raro; Laurent Poirel; Patrice Nordmann; R. Lienhard; L. Vonallmen; C. Schilt; A. Scherler; K. Lucke; M. Jutzi; M. Reichmuth; U. Schibli; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Objectives The occurrence of metallo-beta-lactamase-producing Pseudomonas aeruginosa (MBL-PA) isolates is increasing globally, including in Switzerland. The aim of this study was to characterise, phenotypically and genotypically, the MBL-PA isolates submitted to the Swiss National Reference Center for Emerging Antibiotic Resistance (NARA) reference laboratory over a 12-month period from July 2022 to July 2023. Methods Thirty-nine non-duplicate MBL-PA Isolates were submitted to NARA over the study period from across Switzerland. Susceptibility was determined by broth microdilution according to EUCAST methodology. Whole-genome sequencing was performed on 34 isolates. Sequence types (STs) and resistance genes were ascertained using the Centre for Genomic Epidemiology platform. MBL genes, bla NDM-1 , bla IMP-1 , and bla VIM-2 , were cloned into vector pUCP24 and transformed into P. aeruginosa PA14. Results The most prevalent MBL types identified in this study were VIM (21/39; 53.8%) followed by NDM (11/39; 28.2%), IMP (6/39; 15.4%), and a single isolate produced both VIM and NDM enzymes. WGS identified 13 different STs types among the 39 isolates. They all exhibited resistance to cephalosporins, carbapenems, and the beta-lactam-beta-lactamase inhibitor combinations, ceftolozane-tazobactam, ceftazidime-avibactam, imipenem-relebactam, and meropenem-vaborbactam, and 8 isolates were cefiderocol (FDC) resistant. Recombinant P. aeruginosa strains producing bla NDM-1 , bla IMP-1 , and bla VIM-2 exhibited FDC MICs of 16, 8, and 1 mg/L, respectively. Conclusions This study showed that the MBL-PA in Switzerland could be attributed to the wide dissemination of high-risk clones that accounted for most isolates in this study. Although FDC resistance was only found in 8 isolates, MBL carriage was shown to be a major contributor to this phenotype.

Threatened conservation scientists: The aftermath of an eye-opening publication on rewilding - María de las Mercedes Guerisoli; Mauro I. Schiaffini; Pablo Teta; Alejandro E.J. Valenzuela; Patricia Mirol; Javier Nori; Guillermo E. Defossé; María Marcela Godoy; Pablo Krieger; Tomás Withington; María G. Agostini; Christopher B. Anderson; et al. (Biological Conservation, 2023)

Laboratory simulation of fault reactivation by fluid injection and implications for induced seismicity at the BedrettoLab, Swiss Alps - G. Volpe; G. Pozzi; C. Collettini; E. Spagnuolo; P. Achtziger-Zupančič; A. Zappone; L. Aldega; M.A. Meier; D. Giardini; M. Cocco (Tectonophysics, 2023)

Molecular variability of watermelon mosaic virus isolates from Argentina - E. Pozzi; M. C. Perotto; S. Bertin; A. Manglli; C. Luciani; V. C. Conci; L. Tomassoli (European Journal of Plant Pathology, 2020)

REST-Dependent Presynaptic Homeostasis Induced by Chronic Neuronal Hyperactivity - F. Pecoraro-Bisogni; Gabriele Lignani; A. Contestabile; E. Castroflorio; D. Pozzi; A. Rocchi; C. Prestigio; M. Orlando; P. Valente; M. Massacesi; F. Benfenati; Pietro Baldelli (Molecular Neurobiology, 2018)

Identification and characterization of a new potyvirus infecting cucurbits - M. C. Perotto; E. A. Pozzi; M. G. Celli; C. E. Luciani; M. S. Mitidieri; V. C. Conci (Archives of Virology, 2018)

Activation of insulin-like growth factor 1 receptor participates downstream of GPR30 in estradiol-17β-d-glucuronide-induced cholestasis in rats - Ismael R. Barosso; Gisel S. Miszczuk; Nadia Ciriaci; Romina B. Andermatten; Paula M. Maidagan; Valeria Razori; Diego R. Taborda; Marcelo G. Roma; Fernando A. Crocenzi; Enrique J. Sánchez Pozzi (Archives of Toxicology, 2018)

Occurrence and characterization of a severe isolate of Watermelon mosaic virus from Argentina - María Cecilia Perotto; M. G. Celli; E. A. Pozzi; C. E. Luciani; V. C. Conci (European Journal of Plant Pathology, 2016)

The contribution of sensory nerves to cutaneous vasodilatation of the forearm and leg to local skin heating - Gary J. Hodges; Andrew T. Del Pozzi; Gregory W. McGarr; Matthew M. Mallette; Stephen S. Cheung (European Journal of Applied Physiology, 2015)

Sandwich-cultured rat hepatocytes as an in vitro model to study canalicular transport alterations in cholestasis - Gisel S. Miszczuk; Ismael R. Barosso; Andrés E. Zucchetti; Andrea C. Boaglio; José M. Pellegrino; Enrique J. Sánchez Pozzi; Marcelo G. Roma; Fernando A. Crocenzi (Archives of Toxicology, 2015)

Prevalence of respiratory colonisations and related antibiotic resistances among paediatric tracheostomised patients of a long-term rehabilitation centre in Italy - M. Pozzi; P. Pellegrino; S. Galbiati; M. Granziera; F. Locatelli; C. Carnovale; V. Perrone; S. Antoniazzi; C. Perrotta; S. Strazzer; E. Clementi (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Epidemiological analysis on two decades of hospitalisations for meningitis in the United States - P. Pellegrino; C. Carnovale; V. Perrone; D. Salvati; M. Gentili; T. Brusadelli; S. Antoniazzi; M. Pozzi; S. Radice; E. Clementi (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

The Ca2+-calmodulin-Ca2+/calmodulin-dependent protein kinase II signaling pathway is involved in oxidative stress-induced mitochondrial permeability transition and apoptosis in isolated rat hepatocytes - Flavia D. Toledo; Leonardo M. Pérez; Cecilia L. Basiglio; Justina E. Ochoa; Enrique J. Sanchez Pozzi; Marcelo G. Roma (Archives of Toxicology, 2014)

The Use (and Misuse) of Phylogenetic Trees in Comparative Behavioral Analyses - Luca Pozzi; Christina M. Bergey; Andrew S. Burrell (International Journal of Primatology, 2014)

Physiological concentrations of unconjugated bilirubin prevent oxidative stress-induced hepatocanalicular dysfunction and cholestasis - Cecilia L. Basiglio; Flavia D. Toledo; Andrea C. Boaglio; Sandra M. Arriaga; Justina E. Ochoa; Enrique J. Sánchez Pozzi; Aldo D. Mottino; Marcelo G. Roma (Archives of Toxicology, 2014)

A New Method for Genome-wide Marker Development and Genotyping Holds Great Promise for Molecular Primatology - Christina M. Bergey; Luca Pozzi; Todd R. Disotell; Andrew S. Burrell (International Journal of Primatology, 2013)

Formal infectious diseases consultation is associated with decreased mortality in Staphylococcus aureus bacteraemia - J. O. Robinson; S. Pozzi - Langhi; M. Phillips; J. C. Pearson; K. J. Christiansen; G. W. Coombs; R. J. Murray (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Evaluation of artificial sweat in athletes with spinal cord injuries - R. C. Pritchett; P. A. Bishop; Z. Yang; K. L. Pritchett; J. M. Green; C. P. Katica; A. T. Del Pozzi (European Journal of Applied Physiology, 2010)

UVB radiation induced effects on cells studied by FTIR spectroscopy - Lucia Di Giambattista; P. Grimaldi; S. Gaudenzi; D. Pozzi; M. Grandi; S. Morrone; I. Silvestri; A. Congiu Castellano (European Biophysics Journal, 2010)

Amphibian larvae and zinc sulphate: a suitable model to study the role of brain-derived neurotrophic factor (BDNF) in the neuronal turnover of the olfactory epithelium - Carola A. M. Yovanovich; Lucas D. Jungblut; Tamara Heer; Andrea G. Pozzi; Dante A. Paz (Cell and Tissue Research, 2009)

An Orthotopic Model of Lung Cancer to Analyze Primary and Metastatic NSCLC Growth in Integrin α1-Null Mice - Xiwu Chen; Yan Su; Barbara Fingleton; Heath Acuff; Lynn M. Matrisian; Roy Zent; Ambra Pozzi (Clinical & Experimental Metastasis, 2005)